The Use of Latent Profile Analysis Model in Identifying Prototypes Personality in Saudi Sample - Al-harbi, Khaleel (Jordan Journal of Educational Sciences, 2018)
The purpose of this study is to use latent profile analysis using the Five Factor Model (FFM) in order to identify personality prototypes in a Saudi sample of 948 female students with respect to some variables (educational level, GPA, and major). A 2-profile solution provided the best fit to the Saudi data. The first profile, named Reserved Personality, composed 30.60% of the sample, with low performance in Neuroticism, Extraversion, Openness, Cons-cientiousness, and moderate in Agreeableness. Whereas the second profile, named Resilient Personality, composed 69.40% of the sample, with low performance in Neuroticism, high in Agreeableness, above average in Extraversion and Conscientiousness, and moderate in Openness. The edu-cational level, GPA, and major variables did not show evident impact with the two types of personality (Reserved and Resilient).